Leptin and resistin levels in serum of patients with hematologic malignancies: correlation with clinical characteristic - Pamuk, G.E.; Demir, M.; Harmandar, F.; Yesil, Y.; Turgut, B.; Vural, Ö. (Experimental Oncology, 2006)
Aim:To evaluate leptin and resistin levels in patients with various hematologic malignancies. Methods: We included 21 patients with lymphoma, 14 with multiple myeloma (MM), 14 with acute leukemia, 13 with chronic lymphocytic leukemia (CLL), and 25 healthy control subjects into our study. The subjects’ body mass indexes (BMI) were calculated; hematological and acute phase response parameters, serum lipid were determined; serum leptin and resistin levels were determined by ELISA. Results: Serum leptin level was significantly increased in CLL and MM groups when compared to the control group (p < 0.01). Resistin level was significantly higher in lymphoma patients than in CLL, acute leukemia and control groups (p < 0.01). In the control group, leptin level was negatively correlated with hemoglobin level (r = –0.44, p = 0.047); and in all patients with hematologic malignancies, leptin level was correlated with BMI (r = 0.32, p = 0.02). Leptin in lymphoma subjects correlated with hemoglobin level (r = 0.64, p = 0.005), resistin level correlated with the platelet count in patients with hematologic malignancies (r = 0.26, p = 0.044). In addition, leptin level had negative correlations with international prognostic score (IPS) in Hodgkin lymphoma (r = –0.9, p = 0.002) and with international prognostic index (IPI) in non-Hodgkin lymphoma (r = –0.77, p = 0.03). In CLL patients, leptin level had a correlation with the poor prognostic marker — CD38 level (r = 0.68, p = 0.03). Conclusion: We found higher leptin levels in MM and CLL patients, and higher resistin levels in lymphoma patients: this fact demonstrates that changes in adipose tissue and metabolism occur in these disease states.